1982
DOI: 10.1093/schbul/8.4.587
|View full text |Cite
|
Sign up to set email alerts
|

At Issue: Thought Disorder or Speech Disorder in Schizophrenia?

Abstract: The classification of schizophrenic patients into thought disordered (TD) and non-thought disordered (NTD) is questioned. It is suggested that the terms speech disordered and non-speech disordered are more exact, and that viewing deviant speech structurally with no assumptions as to the thought behind it may prove valuable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 9 publications
2
33
0
1
Order By: Relevance
“…Hence, an implication of this finding is that the absence of social speech is correlated with a reduction in dialogical inner speech, an association that makes sense within the context of Vygotsky’s developmental model (1934), which proposes that the ontogeny of inner speech lies in social speech. The finding of an association between poverty of speech and diminished self-reported dialogical inner speech also informs the longstanding debate of whether TD is a speech or a cognitive problem (Chaika, 1982; Lanin-Kettering and Harrow, 1985). …”
Section: Discussionsupporting
confidence: 53%
“…Hence, an implication of this finding is that the absence of social speech is correlated with a reduction in dialogical inner speech, an association that makes sense within the context of Vygotsky’s developmental model (1934), which proposes that the ontogeny of inner speech lies in social speech. The finding of an association between poverty of speech and diminished self-reported dialogical inner speech also informs the longstanding debate of whether TD is a speech or a cognitive problem (Chaika, 1982; Lanin-Kettering and Harrow, 1985). …”
Section: Discussionsupporting
confidence: 53%
“…Earlier conceptualizations based on aphasia models (1) were later replaced by theories that language dysfunction in schizophrenia reflected an underlying disorder of thought process (2,3). Over the past few decades, there has been increased interest in clarifying whether schizophrenia involves a primary language problem that is independent of formal thought disorder (i.e., deviant language that can be separated from abnormal thoughts [4]). Although it remains unclear to what extent language abnormalities and thought disorder are dissociable (5), there is increasing behavioral evidence that schizophrenia involves a primary disruption in language (e.g., references 6,7).…”
mentioning
confidence: 99%
“…In his maverick way, this author argued that severe formal thought disorder with incoherence, neologisms, etc, and fluent dysphasias had a common basis in disease of the speech areas of the brain. Modern study of this issue has been characterized by polarization of views: on the basis of single case studies, Critchley (1964), a neurologist, concluded that dysphasia and schizophrenic thought disorder were recognizably different; in contrast, Chaika (1982), a linguist, argued that characteristic phonological, syntactical and semantic features of dysphasia could be discerned in thought disordered schizophrenic speech. There has only been one attempt to resolve this debate experimentally.…”
Section: Dr Mckenna (Consultant Psychiatrist)mentioning
confidence: 99%